2022
DOI: 10.3389/fpls.2022.945225
|View full text |Cite
|
Sign up to set email alerts
|

Tissue-targeted inorganic pyrophosphate hydrolysis in a fugu5 mutant reveals that excess inorganic pyrophosphate triggers developmental defects in a cell-autonomous manner

Abstract: Excess PPi triggers developmental defects in a cell-autonomous manner. The level of inorganic pyrophosphate (PPi) must be tightly regulated in all kingdoms for the proper execution of cellular functions. In plants, the vacuolar proton pyrophosphatase (H+-PPase) has a pivotal role in PPi homeostasis. We previously demonstrated that the excess cytosolic PPi in the H+-PPase loss-of-function fugu5 mutant inhibits gluconeogenesis from seed storage lipids, arrests cell division in cotyledonary palisade tissue, and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(14 citation statements)
references
References 102 publications
1
13
0
Order By: Relevance
“…among transgenic lines, consistent with an axial role in the central metabolism of gluconeogenesis CCE (Gunji et al, 2022). These findings not only provide a conceptual framework to unveil metabolic fluctuations within leaf tissues with high spatiotemporal resolution, but also suggest that excess PPi exerts its inhibitory effect in planta during the early stages of seedling establishment in a tissue-and cellautonomous manner.…”
Section: Fugu5-mediated Class II Compensation: Contribution Of Metabo...supporting
confidence: 69%
See 4 more Smart Citations
“…among transgenic lines, consistent with an axial role in the central metabolism of gluconeogenesis CCE (Gunji et al, 2022). These findings not only provide a conceptual framework to unveil metabolic fluctuations within leaf tissues with high spatiotemporal resolution, but also suggest that excess PPi exerts its inhibitory effect in planta during the early stages of seedling establishment in a tissue-and cellautonomous manner.…”
Section: Fugu5-mediated Class II Compensation: Contribution Of Metabo...supporting
confidence: 69%
“…However, the compensatory interplay between cell proliferation and post-mitotic cell expansion during the induction of compensatory cell enlargement (CCE) is ill-known. Because this knowledge on cellular dynamics is instrumental in determining future directions aiming to delineate the holistic mechanisms of compensation, it has been recently investigated using leaves chimeric for the key elements of class I, II, or III compensation ( Kawade et al., 2010 ; Gunji et al., 2022 ) ( Figure 1 ). The above investigations revealed that both cell-autonomous and non-cell autonomous mechanisms are involved in CCE.…”
Section: Underpinnings Of Compensatory Coordination Between Cell Divi...mentioning
confidence: 99%
See 3 more Smart Citations